scFv intrabody targeting wildtype TDP-43 presents protective effects in a cellular model of TDP-43 proteinopathy. - Yara Al Ojaimi; Rudolf Hergesheimer; Anna A Chami; Hugo Alarcan; Johanna Augros; Audrey Dangoumau; Shanez Haouari; Jérôme Bourgeais; Antoine Lefevre; Samira Osman; Patrick Emond; Patrick Vourc'h; et al. (PLoS ONE)
TDP-43 proteinopathies are neurological disorders marked by the abnormal accumulation of TDP-43 in the cytoplasm. This mislocalization disrupts the normal function of the protein. In most cases, it is the wildtype (wt) form of the protein that is involved. An untargeted high-throughput screen of a single-chain variable fragment (scFv) library was performed using phage display against human full-length wt TDP-43. Two scFvs (B1 and D7) were retained following cellular expression (then termed intrabodies) and colocalization with cytoplasmic TDP-43 in vitro. We generated a 3D structure of full length wt TDP-43 in silico, and used it for epitope mapping. In a cellular model of TDP-43 proteinopathy, D7 enhanced the proteasomal degradation of the insoluble 35-kDa C-terminal fragment of TDP-43 and reversed some TDP-43-induced metabolomic alterations, particularly relating to the lipid metabolism. Our findings offer a new scFv intrabody that bind to human wtTDP-43 and modify cellular pathways associated with TDP-43 proteinopathies.